Core resin composition and method for producing sintered body
The resin composition for cores, comprising crosslinked polymer particles and an organic binder with thermoplastic resin, addresses the issue of cavity shape deformation during the formation of sintered bodies with cavities, ensuring accurate and stable cavity formation within the sintered body.
Patent Information
- Application Number
- JP2021056663
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-03-30
AI Technical Summary
When forming a sintered body with a cavity using a 3D printer and material extrusion laminate method, gravity causes the molten material to droop, and during degreasing, the softened laminated structure can deform, leading to cavity shape issues.
A resin composition for cores is developed, comprising crosslinked polymer particles and an organic binder with thermoplastic resin, which supports the cavity shape during degreasing and sintering, preventing drooping and deformation.
The core resin composition effectively prevents drooping and deformation during degreasing and sintering, ensuring accurate formation of cavities within the sintered body, while the crosslinked polymer particles and organic binder can be removed by heat decomposition.
Smart Images

Figure 0007650697000003 
Figure 0007650697000001 
Figure 0007650697000002
Abstract
Description
[Technical field]
[0001] An embodiment of the present invention relates to a core resin composition used as a material for a core to form a cavity inside a sintered body, and a method for producing a sintered body using the same. [Background technology]
[0002] Material Extrusion Deposition Modeling (MEX) (also known as Fused Deposition Modeling: FDM) is known as a technique for manufacturing ceramic products and metal products using a 3D printer. For example, Patent Document 1 proposes that a layered structure is modeled by a material extrusion deposition modeling 3D printer using a compound for 3D printers made by adding an organic binder to inorganic powders such as ceramic powders and metal powders, and then a sintered body is obtained by debinding and sintering. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2020 / 003901 Summary of the Invention [Problem to be solved by the invention]
[0004] When a laminated structure is modeled using a 3D printer that uses a material extrusion lamination method to obtain a sintered body with a hollow portion inside, the hollow portion can be formed by drawing a bridge-shaped modeling path along which a nozzle that ejects molten material moves. However, in this case, the ejected material sags due to gravity. In addition, sagging may occur in the hollow portion due to the softening of the laminated structure during degreasing after modeling. For this reason, it is considered to use a core that supports the shape of the hollow portion to prevent sagging. It is desirable for such a core to be modeled together with the laminated structure by the 3D printer and removed during the degreasing or sintering process after modeling.
[0005] In view of the above, an embodiment of the present invention aims to provide a resin composition that can form a cavity inside a sintered body when a layered structure produced by a 3D printer is degreased and sintered to produce a sintered body, and that can provide a core that is suitable for degreasing. [Means for solving the problem]
[0006] The present invention includes the embodiments set forth below. [1] A resin composition used as a material for a core to form a cavity inside a sintered body when a laminated structure is formed by a three-dimensional printer using a composition for sintered bodies containing an inorganic powder and an organic binder, and the laminated structure is degreased and sintered to produce a sintered body, the resin composition for core containing crosslinked polymer particles (A) and an organic binder (B) containing a thermoplastic resin (B1). [2] The resin composition for a core according to [1], wherein the thermoplastic resin (B1) contains a thermoplastic resin (B10) having a thermal decomposition temperature lower than the thermal decomposition temperature of the crosslinked polymer particles (A). [3] The resin composition for a core according to [1] or [2], wherein the crosslinked polymer particles (A) have a thermal decomposition temperature higher than the thermal decomposition temperature of at least one thermoplastic resin contained in the organic binder of the composition for a sintered body. [4] The resin composition for a core according to any one of [1] to [3], wherein the crosslinked polymer particles (A) have a thermal decomposition temperature lower than the maximum temperature during degreasing of the laminate structure. [5] The resin composition for a core according to any one of [1] to [4], wherein a mass ratio of the crosslinked polymer particles (A) to the organic binder (B) is (A) / (B)=100 / 35 to 100 / 105. [6] The resin composition for a core according to any one of [1] to [5], which has a residue of less than 0.1 mass % when heated in air at 1000°C. [7] A method for producing a sintered body made of ceramics, cermet or metal, comprising: forming a laminated structure by a three-dimensional printer using a composition for sintered bodies containing an inorganic powder and an organic binder; forming a core by a three-dimensional printer using a resin composition for a core described in any one of [1] to [6]; heating the laminated structure together with the core in a state in which the core is placed inside the laminated structure to degrease the laminated structure; and sintering the degreased laminated structure to obtain a sintered body having a hollow portion inside. [8] A method for producing a sintered body according to [7], comprising using the composition for sintered body and the resin composition for core to form the laminated structure together with the core, which is placed inside the laminated structure, using a three-dimensional printer. Effect of the Invention
[0007] In the case of the core resin composition according to an embodiment of the present invention, by blending crosslinked polymer particles together with an organic binder containing a thermoplastic resin, it is possible to form a hollow portion inside the sintered body while suppressing sagging during degreasing, and to provide a core that is suitable for degreasing. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1A is a plan view of a laminated structure in an example, and FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The resin composition for a core according to the embodiment contains crosslinked polymer particles (A) and an organic binder (B) containing a thermoplastic resin (B1), and is used as a material for a core for forming a cavity inside a sintered body when a laminated structure is molded by a 3D printer using a composition for a sintered body containing an inorganic powder and an organic binder, and the laminated structure is degreased and sintered to produce a sintered body. By providing the core, the inner wall surface of the laminated structure that becomes the cavity can be supported by the core, and sagging during molding can be prevented.
[0010] In addition, degreasing is a process in which the laminated structure is heated to thermally decompose and remove the organic binder in the laminated structure. During degreasing, the thermoplastic resin contained in the laminated structure softens, making the laminated structure more likely to deform, while as the degreasing approaches completion, the laminated structure is given strength that allows it to maintain its shape even without a core. According to this embodiment, crosslinked polymer particles (A) are used for the core, and unlike thermoplastic resins, the crosslinked polymer particles (A) do not plasticize when heated, so that the laminated structure, which is easily deformed, can be supported in the degreasing process and deformation of the laminated structure can be suppressed. In addition, the crosslinked polymer particles (A) and organic binder (B) that constitute the core are organic, so they can be removed by thermal decomposition in the degreasing process or sintering process.
[0011] The crosslinked polymer particles (A) are fine resin particles having a crosslinked structure, and examples thereof include crosslinked acrylic resin particles, crosslinked urethane resin particles, and crosslinked styrene resin particles, and these can be used alone or in combination of two or more kinds.
[0012] The crosslinked acrylic resin particles are crosslinked particles having a (meth)acrylic acid ester monomer as the main constituent unit (50% by mass or more of the constituent units; the same applies below). Examples of the crosslinked acrylic resin particles include particles of crosslinked poly(alkyl(meth)acrylate) (the number of carbon atoms in the alkyl group is preferably 4 or less), such as crosslinked poly(methyl(meth)acrylate), crosslinked poly(ethyl(meth)acrylate), crosslinked poly(propyl(meth)acrylate), and crosslinked poly(butyl(meth)acrylate, and may also be crosslinked acrylic copolymer particles containing other monomers such as styrene as copolymerization components. Here, "(meth)acrylate" refers to acrylate or methacrylate, and "(meth)acrylic acid" refers to acrylic acid or methacrylic acid.
[0013] The crosslinked urethane resin particles are crosslinked particles composed of a urethane resin having a urethane bond and / or a urea bond. The crosslinked styrene resin particles are crosslinked particles having a styrene monomer as a main constituent unit.
[0014] The crosslinked polymer particles (A) are preferably spherical particles, i.e., crosslinked polymer beads, and more preferably spherical particles. The average particle size of the crosslinked polymer particles (A) is not particularly limited, but is preferably 1 to 200 μm, more preferably 1 to 50 μm, and even more preferably 1 to 30 μm. In this specification, the average particle size means the particle size at an integrated value of 50% in the particle size distribution obtained using a Coulter counter (for example, a precision particle size distribution measuring device sold by Beckman Coulter, Inc.).
[0015] The crosslinked polymer particles (A) preferably have a thermal decomposition temperature higher than that of at least one thermoplastic resin contained in the organic binder (D) of the composition for sintered bodies described later. That is, the organic binder (D) of the composition for sintered bodies contains one or more thermoplastic resins, and the crosslinked polymer particles (A) preferably have a thermal decomposition temperature higher than that of at least one of the thermoplastic resins. By having such a high thermal decomposition temperature, the laminate structure formed by the composition for sintered bodies can be supported up to a temperature at which the laminate structure does not deform when degreasing the laminate structure, and deformation of the laminate structure can be effectively suppressed.
[0016] The thermal decomposition temperature of the crosslinked polymer particles (A) is preferably lower than the maximum temperature during degreasing of the laminate structure, so that the crosslinked polymer particles (A) can be removed by thermal decomposition during the degreasing step of the laminate structure.
[0017] The thermal decomposition temperature of the crosslinked polymer particles (A) is preferably 200 to 600° C., more preferably 230 to 550° C., and further preferably 250 to 500° C. In this specification, the thermal decomposition temperature can be measured using a differential thermal analyzer (for example, a thermogravimetric / differential thermal analyzer sold by Rigaku Corporation) in an aluminum pan with a diameter of 5 mm and a height of 2.5 mm, under an air flow of 200 mL / min, with a temperature increase of 10° C. / min, and the value at 50% by mass of the total weight loss is determined as the thermal decomposition temperature.
[0018] The organic binder (B) contained in the core resin composition contains a thermoplastic resin (B1). Examples of the thermoplastic resin (B1) include non-crystalline polymers such as acrylic resins, atactic polystyrene (atactic PS), polycarbonate (PC), amorphous polyolefins, and acrylonitrile-butadiene-styrene (ABS), and crystalline polymers such as ethylene-vinyl acetate copolymer (EVA), polyethylene (PE), polypropylene (PP), polyacetal (POM), polyamide (PA), polybutylene terephthalate (PBT), polyethylene terephthalate (PET), and polylactic acid (PLA). These can be used alone or in combination of two or more.
[0019] Among these, it is preferable to use at least one thermoplastic resin (B11) selected from non-crystalline polymers and EVA as the thermoplastic resin (B11), and the thermoplastic resin (B11) may be used as the main component in combination with at least one thermoplastic resin (B12) selected from crystalline polymers other than EVA.
[0020] The ratio of the thermoplastic resin (B11) contained in the thermoplastic resin (B1) is not particularly limited, but is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more.
[0021] As the thermoplastic resin (B11), it is preferable to use two or more kinds selected from the group consisting of an acrylic resin, atactic PS, amorphous polyolefin, and EVA. It is more preferable to use an acrylic resin and at least one kind selected from the group consisting of atactic PS, amorphous polyolefin, and EVA.
[0022] As the thermoplastic resin (B12), it is preferable to use PP and / or POM.
[0023] The thermoplastic resin (B1) used in the core resin composition is preferably the same type as the thermoplastic resin used in the sintered body composition described below. Therefore, when a ceramic powder such as a metal oxide powder or a cermet powder is used as the inorganic powder of the sintered body composition, it is preferable to use an acrylic resin and atactic PS in combination as the thermoplastic resin (B1), which may be combined with EVA and / or amorphous polyolefin, and more preferably, the acrylic resin, atactic PS, and EVA in combination. The mass ratio of these is preferably 20 to 100 parts by mass, more preferably 30 to 80 parts by mass, of atactic PS relative to 100 parts by mass of the acrylic resin. In addition, when EVA is used, it is preferably 5 to 200 parts by mass, more preferably 10 to 50 parts by mass, relative to 100 parts by mass of the acrylic resin.
[0024] When a metal powder is used as the inorganic powder of the composition for sintered body, it is preferable to use an acrylic resin and EVA in combination as the thermoplastic resin (B1), and further to combine atactic PS and / or PP. The mass ratio of these is preferably 10 to 200 parts by mass, more preferably 80 to 150 parts by mass, 0 to 200 parts by mass, more preferably 50 to 150 parts by mass, of atactic PS, and 0 to 200 parts by mass, more preferably 30 to 100 parts by mass, relative to 100 parts by mass of the acrylic resin.
[0025] Examples of the acrylic resin include a polymer of a (meth)acrylic acid ester, which is an ester of (meth)acrylic acid and an alcohol having 1 to 8 carbon atoms, and a copolymer of a (meth)acrylic acid ester and another monomer. The weight average molecular weight (Mw) of the acrylic resin is not particularly limited, and may be, for example, about 10,000 to 350,000, or about 20,000 to 100,000. In this specification, the weight average molecular weight can be measured by using GPC (gel permeation chromatography).
[0026] Specific examples of (meth)acrylic acid esters include n-alkyl (meth)acrylates in which the alkyl group has 1 to 8 carbon atoms, isopropyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, etc. Among these, at least one selected from the group consisting of n-alkyl (meth)acrylates in which the alkyl group has 1 to 4 carbon atoms, such as methyl (meth)acrylate and n-butyl (meth)acrylate, isopropyl (meth)acrylate, and isobutyl (meth)acrylate is preferred.
[0027] Examples of copolymers of (meth)acrylic acid esters and other monomers include composite acrylic resins obtained by dispersing a solution of an ethylene-vinyl acetate copolymer or an ethylene-ethyl acrylate copolymer, a (meth)acrylic acid ester alone or a mixture of a (meth)acrylic acid ester and a styrene-based monomer, and a polymerization initiator in an aqueous medium containing a dispersant and subjecting the solution to suspension polymerization, as described in JP-A-2000-303103.
[0028] As the atactic PS, one having a weight average molecular weight (Mw) of about 100,000 to 300,000 is preferably used, and one having a weight average molecular weight (Mw) of about 150,000 to 250,000 is more preferably used.
[0029] It is more preferable to use EVA with a low degree of crystallinity (for example, a degree of crystallinity of 25% or less). Since the degree of crystallinity of EVA correlates with the vinyl acetate (VA) content, a preferable example of EVA is EVA with a vinyl acetate content (mass percentage: JISK7192:1999) of 20% to 50%, more preferably 25% to 40%. In addition, it is preferable to use EVA with a weight average molecular weight of about 30,000 to 120,000, and more preferably about 50,000 to 100,000.
[0030] The PP to be used preferably has a weight average molecular weight of about 100,000 to 400,000, and more preferably has a weight average molecular weight of about 200,000 to 300,000.
[0031] As the thermoplastic resin (B1), it is preferable to use a thermoplastic resin (B10) having a thermal decomposition temperature lower than that of the crosslinked polymer particles (A). Since the thermal decomposition temperature of the crosslinked polymer particles (A) is high, the laminate structure can be supported up to a temperature at which the laminate structure does not deform when degreasing the laminate structure, and deformation of the laminate structure in the degreasing step can be effectively suppressed. When using a plurality of types of thermoplastic resins (B1), all of the thermoplastic resins (B1) may be the above-mentioned thermoplastic resin (B10), but a thermoplastic resin (B100) having a thermal decomposition temperature equal to or higher than the thermal decomposition temperature of the crosslinked polymer particles (A) may be partially included. In that case, it is preferable that 30% by mass or more of the thermoplastic resin (B1) is the above-mentioned thermoplastic resin (B10), more preferably 35% by mass or more of the thermoplastic resin (B1), and 40 to 70% by mass of the thermoplastic resin (B10) may be the above-mentioned thermoplastic resin (B10).
[0032] The content of the thermoplastic resin (B1) in the organic binder (B) is not particularly limited, but from the viewpoints of suppressing stringing during modeling with a 3D printer (stringing that occurs when the nozzle that ejects the molten composition is moved to the next layer position after layer-by-layer modeling) and suppressing deformation during the degreasing process, the content is preferably 35 to 85 mass%, and more preferably 40 to 80 mass%.
[0033] The organic binder (B) preferably contains a wax (B2) to improve the fluidity of the core resin composition. The wax (B2) may be synthetic or natural, and specific examples thereof include paraffin wax, microcrystalline wax, polyethylene wax, beeswax, carnauba wax, montan wax, polyalkylene glycol, etc., and any one or more of these may be used in combination. The content of the wax (B2) in the organic binder (B) is not particularly limited, and may be 7 to 40 mass%, 7 to 35 mass%, 10 to 30 mass%, or 15 to 25 mass%.
[0034] The organic binder (B) may contain a lubricant (B3) to improve the fluidity of the core resin composition. Specific examples of the lubricant (B3) include fatty acids and their derivatives (esters, amides, etc.), and these may be used alone or in combination of two or more. Preferred lubricants include stearic acid and its esters (for example, sorbitan monostearate). The content of the lubricant (B3) in the organic binder (B) is not particularly limited, and may be 0 to 18 mass%, 0 to 16 mass%, or 0 to 15 mass%.
[0035] The organic binder (B) may contain other additives (B4). Examples of the other additives (B4) include plasticizers, antioxidants, metal deactivators, ultraviolet absorbers, and nucleating agents.
[0036] Examples of the plasticizer include phthalates, adipic esters, trimellitic esters, 1,2-cyclohexanedicarboxylate diisononyl ester, 4-cyclohexene-1,2-dicarboxylate bis(2-ethylhexyl), benzoic acid glycol esters, phosphate esters, etc. Examples of the antioxidant include phenol-based antioxidants.
[0037] In the core resin composition, the mass ratio of the crosslinked polymer particles (A) to the organic binder (B) is preferably (A) / (B)=100 / 35-100 / 105. By using 35 parts by mass or more of the organic binder (B) per 100 parts by mass of the crosslinked polymer particles (A), the fluidity of the core resin composition can be increased during additive manufacturing using a three-dimensional printer, and the adhesion between the core resin compositions can be increased, and the adhesion between the core resin composition and the composition for sintered body can be increased, thereby improving the modeling properties using a three-dimensional printer. In addition, by using 105 parts by mass or less of the organic binder (B), the supportability in the degreasing process can be improved. A more preferable mass ratio is (A) / (B)=100 / 40-100 / 100, and even more preferably (A) / (B)=100 / 45-100 / 95.
[0038] In order to prevent the residue from remaining after the sintering process, the core resin composition preferably has a residue (heating residue) of less than 0.1% by mass when heated at 1000°C in air, more preferably less than 0.05% by mass. This allows the residue in the cavity after the sintering process to be reduced. In particular, when a sealed space is formed as the cavity, the residue in the cavity cannot be removed after sintering. Therefore, it is preferable that the heating residue is as small as possible. In order to reduce or eliminate the heating residue in this way, it is sufficient to reduce the amount of inorganic elements contained in the core resin composition so that inorganic elements are not contained. For example, the content of inorganic elements by standard addition method using ICP-MS (inductively coupled plasma mass spectrometry) is preferably less than 0.1% by mass, more preferably less than 0.05% by mass. Here, the inorganic element is an element other than oxygen, carbon, hydrogen, and nitrogen, and refers to an element that remains as a residue after sintering, such as sodium, potassium, calcium, magnesium, phosphorus, and sulfur.
[0039] The method for producing the resin composition for the core is not particularly limited, and the composition can be prepared by melt-kneading the crosslinked polymer particles (A) and the organic binder (B). Examples of the kneader used for melt-kneading include a pressure kneader, a double-arm kneader, a Banbury kneader, and a single-screw or twin-screw kneading extruder.
[0040] The shape of the core resin composition is not particularly limited, but in one embodiment it may be in pellet form. For example, the molten material extruded after kneading may be cut into pellets in the air using a rotary cutter to form pellets.
[0041] The resin composition for a core according to this embodiment is used as a material for a core when a layered structure is molded by a three-dimensional printer using a composition for a sintered body to produce a sintered body made of an inorganic material such as a ceramic, a cermet, or a metal.
[0042] The composition for sintered body contains an inorganic powder (C) and an organic binder (D). Although there are no particular limitations, one embodiment of the composition for sintered body may be that described in Patent Document 1.
[0043] Specifically, examples of the inorganic powder (C) include metal powder, ceramic powder, and cermet powder. Specific examples of the metal powder include powders of pure iron, iron-nickel, iron-cobalt, iron-silicon, iron-based alloys such as stainless steel, tungsten, aluminum alloys, copper, and copper alloys. Examples of the ceramic powder include powders of oxides such as Al2O3, BeO, and ZrO2, carbides such as TiC, ZrC, B4C, and tungsten carbide (WC), borides such as CrB2 and ZrB2, and nitrides such as TiN and ZrN. Examples of the cermet powder include powders of cemented carbide (such as WC-Co-based alloys), Al2O3-Fe-based, TiC-Ni-based, TiC-Co-based, and B4C-Fe-based. These may be used alone or in combination of two or more.
[0044] The average particle size of the inorganic powder (C) is not particularly limited and may be, for example, 0.05 to 30 μm or 0.1 to 10 μm. In this specification, the average particle size of the inorganic powder (C) means the particle size at an integrated value of 50% in the particle size distribution determined by a laser diffraction / scattering method (Microtrac particle size measuring device: MT3100II).
[0045] The organic binder (D) contains a thermoplastic resin (D1) and may further contain a wax (D2), a lubricant (D3) and other additives (D4). In order to match the degreasing patterns of the laminated structure made of the composition for sintered body and the core made of the resin composition for core, it is preferable that the organic binder (D) of the composition for sintered body and the organic binder (B) of the resin composition for core are composed of the same components.
[0046] The thermoplastic resin (D1) is the same as the thermoplastic resin (B1) used in the core resin composition, and examples of the thermoplastic resin (D1) include non-crystalline polymers such as acrylic resins, atactic PS, PC, amorphous polyolefin, and ABS, and crystalline polymers such as EVA, PE, PP, POM, PA, PBT, PET, and PLA. As described above, the thermoplastic resin (D1) used in the composition for sintered body and the thermoplastic resin (B1) used in the core resin composition are preferably the same components, and therefore the preferred resins and combinations of thermoplastic resin (D1) are as described for the thermoplastic resin (B1).
[0047] For example, when a ceramic powder such as a metal oxide powder or a cermet powder is used as the inorganic powder (C), it is preferable to use an acrylic resin and atactic PS in combination as the thermoplastic resin (D1), which may be combined with EVA and / or amorphous polyolefin, and more preferably, the acrylic resin, atactic PS, and EVA in combination. The mass ratio of these is preferably 20 to 100 parts by mass, more preferably 30 to 80 parts by mass, of atactic PS relative to 100 parts by mass of the acrylic resin. Furthermore, when EVA is used, it is preferably 5 to 200 parts by mass, more preferably 7 to 100 parts by mass, and even more preferably 10 to 50 parts by mass, relative to 100 parts by mass of the acrylic resin.
[0048] When a metal powder is used as the inorganic powder (C), it is preferable to use an acrylic resin and EVA in combination as the thermoplastic resin (D1), and further to combine atactic PS and / or PP. The mass ratio of these is preferably 30 to 200 parts by mass, more preferably 80 to 150 parts by mass, 0 to 200 parts by mass, more preferably 50 to 150 parts by mass, of atactic PS, and 0 to 200 parts by mass, more preferably 30 to 100 parts by mass, per 100 parts by mass of the acrylic resin.
[0049] Specific examples and content ratios of the wax (D2), lubricant (D3) and other additives (D4) are the same as those explained for the wax (B2), lubricant (B3) and other additives (B4) used in the core resin composition.
[0050] In the composition for sintered bodies, the mass ratio of the inorganic powder (C) to the organic binder (D) is preferably (C) / (D)=100 / 3 to 100 / 30. For example, when the inorganic powder (A) is a ceramic powder, the mass ratio is preferably (A) / (B)=100 / 10 to 100 / 25, more preferably 100 / 12 to 100 / 20. When the inorganic powder (A) is a metal powder or a cermet powder, the mass ratio is preferably (A) / (B)=100 / 3 to 100 / 13, more preferably 100 / 4 to 100 / 10.
[0051] The resin composition for a core according to the embodiment is used to form a core for forming a cavity by a three-dimensional printer when a laminate structure is formed by a three-dimensional printer using a composition for a sintered body. Therefore, the method for producing a sintered body according to the embodiment may include forming a laminate structure by a three-dimensional printer using a composition for a sintered body, forming a core by a three-dimensional printer using a resin composition for a core, heating the laminate structure together with the core in a state in which the core is disposed inside the laminate structure to degrease it, and sintering the degreased laminate structure to obtain a sintered body having a cavity inside.
[0052] Preferably, the core is a thermodecomposable core that is molded together with the laminated structure by a three-dimensional printer so as to be placed inside the laminated structure, and is thermodecomposable in the degreasing or sintering step after molding, so that a cavity can be formed inside the sintered body. Therefore, a method for manufacturing a sintered body according to a preferred embodiment includes the following steps. (1) A process of forming a laminated structure together with a core by a three-dimensional printer using the above-mentioned resin composition for a core and a composition for a sintered body; (2) a step of heating and degreasing the laminated structure together with the core; and (3) Sintering the degreased laminated structure.
[0053] As a 3D printer, for example, one that can heat and fluidize a molding material, eject it from a nozzle, and layer it to create a 3D structure can be used, and examples of such printers include various 3D printers that use the material extrusion deposition model (MEX) (fused deposition model: FDM) method.
[0054] In step (1), a three-dimensional printer equipped with multiple nozzles is used to heat and fluidize the composition for sintered body and the resin composition for core, respectively, and extrude them from the nozzles, while layer-forming the laminated structure from the composition for sintered body and the core from the resin composition for core, based on data. This results in a laminated structure in which the core is disposed in a portion that is to become a cavity inside the laminated structure, and sagging of the inner wall surface of the laminated structure during modeling can be suppressed. In one embodiment, when forming an enclosed space isolated from the outside as the cavity, the core is formed in a state buried in the laminated structure so as not to appear on the surface of the laminated structure.
[0055] The heating temperature when fluidizing the composition for sintered body and the resin composition for core is not particularly limited as long as these compositions can be fluidized without thermal decomposition, and may be, for example, 100 to 200°C.
[0056] In step (2), the laminated structure having the core thus obtained is heated and degreased. The degreasing step is usually a step for removing organic matter by pyrolysis, so that the organic binder (D) contained in the laminated structure and the crosslinked polymer particles (A) and organic binder (B) contained in the core are also removed by pyrolysis. Note that the crosslinked polymer particles (A) may remain after the degreasing step as long as they can be eliminated in the subsequent sintering step, but it is preferable that they are eliminated after the degreasing step.
[0057] In the debinding step, the thermoplastic resin (D1) contained in the laminated structure softens, making the laminated structure more likely to deform. On the other hand, as the debinding step approaches completion, the laminated structure is given strength that allows it to maintain its shape even without the core. According to this embodiment, the crosslinked polymer particles (A) used in the core are not plasticized by heating, so that the inner wall surface of the laminated structure can be supported up to a temperature at which the laminated structure is less likely to deform in the debinding step, and sagging can be suppressed. In addition, the crosslinked polymer particles (A) and organic binder (B) that constitute the core can be removed by thermal decomposition in the debinding step or sintering step, so there is no need to remove the core.
[0058] The degreasing conditions can be appropriately set depending on the type of inorganic powder (C) contained in the laminated structure. For example, when the inorganic powder (C) is a ceramic powder such as zirconia or alumina, the degreasing may be performed by increasing the temperature in air to about 450 to 550°C at a rate of 5 to 20°C / h. When the inorganic powder (C) is a metal powder, the degreasing may be performed in an inert gas atmosphere by increasing the temperature to about 450 to 550°C at a rate of 5 to 20°C / h.
[0059] In step (3), the laminated structure after the debinding step is sintered. Sintering conditions can be appropriately set depending on the type of inorganic powder (C), etc. For example, when the inorganic powder (C) is a ceramic powder such as zirconia or aluminum, sintering may be performed by increasing the temperature to 1300 to 1700°C at a rate of 40 to 120°C / h in air. When the inorganic powder is a metal powder or a cermet powder, sintering may be performed by increasing the temperature to 1300 to 1400°C at a rate of 40 to 160°C / h in an inert gas atmosphere.
[0060] By carrying out sintering in this manner, a sintered body made of ceramics, cermet or metal is obtained.
[0061] In this embodiment, by using the above-mentioned core, support can be provided not only during modeling using a 3D printer, but also during degreasing. After sintering, the core disappears due to thermal decomposition, so that a cavity corresponding to the shape of the core can be formed inside the sintered body. Therefore, it is possible to form a closed cavity with a complex shape.
[0062] In addition, the various numerical ranges including the above-mentioned blending amounts and viscosities can be arbitrarily combined with their upper and lower limits, and all such combinations are considered to be preferred numerical ranges and are described in this specification. EXAMPLES
[0063] The present invention will be explained in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0064] <Raw materials used> The raw materials used in the examples and comparative examples are as follows.
[0065] [Crosslinked polymer particles] ·Crosslinked acrylic resin particle 1: “MBX-20” manufactured by Sekisui Plastics Co., Ltd. (average particle size: 20 μm, thermal decomposition temperature: 270°C) ·Crosslinked acrylic resin particles 2: “MBX-30” manufactured by Sekisui Plastics Co., Ltd. (average particle size: 30 μm, thermal decomposition temperature: 270°C) ·Crosslinked acrylic resin particles 3: “SSX-102” manufactured by Sekisui Plastics Co., Ltd. (average particle size: 2 μm, thermal decomposition temperature: 270°C) Cross-linked acrylic resin particles 4: "Cross-linked acrylic beads J-6PF" manufactured by Negami Chemical Industries Co., Ltd. (average particle size: 4 μm, thermal decomposition temperature: 270°C) Cross-linked acrylic resin particles 5: "Cross-linked acrylic beads SE-020T" manufactured by Negami Chemical Industries Co., Ltd. (average particle size: 20 μm, thermal decomposition temperature: 300°C) Cross-linked urethane resin particles: "C-400T cross-linked urethane beads" manufactured by Negami Chemical Industries Co., Ltd. (average particle size: 15 μm, thermal decomposition temperature: 320°C) ·Cross-linked styrene resin particles: “SBX-12” manufactured by Sekisui Plastics Co., Ltd. (average particle size: 12 μm, thermal decomposition temperature: 300°C)
[0066] [Thermoplastic resin] Acrylic resin: n-butyl methacrylate, weight average molecular weight 50,000, thermal decomposition temperature 250℃ Atactic PS: Weight average molecular weight 190,000, thermal decomposition temperature 350℃ EVA: Vinyl acetate content 28% by mass, weight average molecular weight 70,000, thermal decomposition temperature 400℃ ·PP: Weight average molecular weight 240,000, thermal decomposition temperature 250℃
[0067] [wax] Paraffin wax: molecular weight 472, melting point 70℃ [Lubricant] Stearic acid: molecular weight 284 [Other additives] Plasticizer: 4-cyclohexene-1,2-dicarboxylate bis(2-ethylhexyl), molecular weight 394
[0068] [Inorganic powder] Alumina powder: BET specific surface area is 6m 2 / g, average particle diameter D 50 is 0.52μm Zirconia powder: Yttria partially stabilized zirconia powder containing 3 mol% Y2O3, BET specific surface area is 15m 2 / g, average particle diameter D 50 is 0.15μm Stainless steel powder: SUS316L, average particle size D 50 is 7.1μm, tap density 4.6g / cm 3 ) ·WC-Co powder: average particle size D 50 is 1.4μm
[0069] <Preparation of Composition for Sintered Body> A composition for sintered body was prepared according to the composition (parts by mass) shown in the following Table 1. In detail, the components shown in Table 1 were melt-kneaded at 170°C using a pressure kneader, and pellets were produced from the resulting melt using a pelletizer-type plunger extruder.
[0070] [Table 1]
[0071] <Preparation of Core Resin Composition> A resin composition for a core was prepared according to the composition (parts by mass) shown in the following Table 2. In detail, the components shown in Table 2 were melt-kneaded at 170°C using a pressure kneader, and pellets were produced from the resulting melt using a pelletizer-type plunger extruder.
[0072] The heat residue of the obtained core resin composition was measured. The heat residue was calculated by heating the core resin composition in air at 1000°C for 2 hours and calculating the ratio of the mass after heating to the mass before heating as the heat residue (mass%).
[0073] <Modeling of laminated structures using 3D printers> In order to produce a sintered body with a hollow portion (flow path), pellets of the composition for sintered body and the resin composition for core prepared above were used to print a laminated structure with a core placed inside as shown in Figure 1 using a 3D printer.
[0074] In detail, a MEX-type three-dimensional printer (CERA#P3 manufactured by S.Lab Co., Ltd., modeling area X150mm×Y150mm×Z150mm, screw diameter φ20mm) equipped with an extrusion device having a first and second pellet inlet was used, and the composition for sintered body was put into the first inlet, and the resin composition for core was put into the second inlet. While the composition for sintered body and the resin composition for core were each discharged from the nozzle, a three-dimensional structure including a laminated structure made of the composition for sintered body and a core made of the resin composition for core was laminated and manufactured. The three-dimensional structure produced was a 50mm×50mm×thickness 6mm laminated structure shown in FIG. 1, inside which a cross-shaped core of width 10mm×height 2mm was integrated. The nozzle diameter was 1.0mm, the nozzle temperature was 150-190°C, the layer pitch was 0.2mm, and the modeling speed was 2000mm / min. The combination of the composition for sintered body and the resin composition for core is as shown in Table 2.
[0075] The core resin composition was evaluated for its adhesiveness during additive manufacturing. The adhesiveness was evaluated based on whether or not the core resin composition adheres to itself during additive manufacturing, and whether or not the core resin composition adheres to the sintered body composition. The evaluation criteria were as follows: ◯: The adhesion between the core resin compositions, and the adhesion between the core resin composition and the sintered body composition are both good. Δ: Poor adhesion occurs between the resin composition for the core and the composition for the sintered body. ×: Poor adhesion occurs between the core resin compositions
[0076] <Degreasing of laminated structures> The three-dimensional structures with the core obtained above were degreased. In the case of those using alumina powder or zirconia powder as the inorganic powder of the laminated structure, the degreasing was performed by increasing the temperature to 500°C at a rate of 10°C / h in air. In the case of those using SUS powder or WC-Co powder as the inorganic powder of the laminated structure, the degreasing was performed by increasing the temperature to 500°C at a rate of 10°C / h in a nitrogen gas atmosphere.
[0077] <Sintering of the layered product> The laminated structure was degreased and then sintered. The laminated structure using alumina powder as the inorganic powder was fired in the atmosphere at a temperature rise rate of 100°C / h to a maximum temperature of 1600°C, and kept at 1600°C for 2 hours. The laminated structure using zirconia powder was fired in the atmosphere at a temperature rise rate of 100°C / h to a maximum temperature of 1350°C, and kept at 1350°C for 2 hours. The laminated structure using SUS powder as the inorganic powder was fired in a vacuum at a temperature rise rate of 150°C / h to 1000°C, and from 1000°C, it was fired in an argon atmosphere at a temperature rise rate of 150°C / h to 1350°C, and kept at 1350°C for 2 hours. For those using WC-Co powder, the temperature was raised to 1000°C in a vacuum at a rate of 150°C / h, and from 1000°C it was raised to 1390°C at a rate of 150°C / h in an argon atmosphere, and then kept at 1390°C for 2 hours.
[0078] The support provided by the core was evaluated by whether or not the cavity was accurately formed after sintering. The evaluation was performed by measuring how much the upper wall of the cavity was deformed downward from the shape before degreasing. The evaluation criteria were as follows: ◯: The deformation after sintering is 0.5 mm or less. △: Deformation of more than 0.5 mm and less than 2 mm is observed after sintering. ×: After sintering, the upper wall of the cavity was attached to the bottom surface and deformation of 2 mm or more was observed.
[0079] After degreasing, the amount of residue of the core resin composition was measured, and the mass ratio of the residue to the core resin composition before degreasing was determined.
[0080] [Table 2]
[0081] The results are shown in Table 2. In Comparative Examples 1 and 2, in which crosslinked polymer particles were not blended into the core resin composition, the support provided by the core during debinding and sintering was impaired, and deformation was observed in the hollow parts. In contrast, in Examples 1 to 10, in which crosslinked polymer particles and an organic binder were blended into the core resin composition, adhesion during additive manufacturing was excellent, as was support provided by the core during debinding and sintering, making it possible to produce sintered bodies with internal hollow parts. Furthermore, in Examples 1 to 10, cores with little residue after debinding and excellent disappearance were produced.
[0082] Although several embodiments of the present invention have been described above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the gist of the invention. These embodiments and their omissions, substitutions, modifications, etc. are included in the scope and gist of the invention as well as the invention and its equivalents described in the claims.
Claims
1. A resin composition used as a core material for forming a hollow portion inside a sintered body when a laminated structure is modeled by a three-dimensional printer using a composition for a sintered body containing an inorganic powder and an organic binder, and the laminated structure is degreased and sintered to produce a sintered body, The present invention comprises crosslinked polymer particles (A) and an organic binder (B) containing a thermoplastic resin (B1), the thermoplastic resin (B1) comprises a thermoplastic resin (B10) having a thermal decomposition temperature lower than the thermal decomposition temperature of the crosslinked polymer particles (A); the crosslinked polymer particles (A) have a thermal decomposition temperature higher than the thermal decomposition temperature of at least one thermoplastic resin contained in the organic binder of the composition for sintering; Resin composition for cores.
2. 2. The resin composition for a core according to claim 1, wherein the crosslinked polymer particles (A) have a thermal decomposition temperature lower than the maximum temperature during degreasing of the laminated structure.
3. The resin composition for a core according to claim 1 or 2, wherein the mass ratio of the crosslinked polymer particles (A) to the organic binder (B) is (A) / (B)=100 / 35 to 100 / 105.
4. The resin composition for a core according to any one of claims 1 to 3, which has a residue of less than 0.1 mass% when heated in air at 1000°C.
5. A method for producing a sintered body made of ceramics, cermet, or metal, comprising the steps of: A method for producing a sintered body, comprising: forming a laminated structure by a three-dimensional printer using a composition for a sintered body containing an inorganic powder and an organic binder; forming a core by a three-dimensional printer using the resin composition for a core according to any one of claims 1 to 4; heating the laminated structure together with the core in a state in which the core is disposed inside the laminated structure to degrease the laminated structure; and sintering the degreased laminated structure to obtain a sintered body having a hollow portion inside.
6. The method for producing a sintered body according to claim 5, wherein the composition for the sintered body and the resin composition for the core are used to form the laminated structure together with the core, the core being disposed inside the laminated structure, by a three-dimensional printer.
Citation Information
Patent Citations
3D printing technique
JP1995507508A
Method of forming pore in sintered product, and sintered product
JP2005048230A
Method of manufacturing sleeve for fluid-dynamic bearing, and sleeve for fluid-dynamic bearing
JP2008241030A
Sintering method
JP2011144419A
Method for making hybrid ceramic / metal, ceramic / ceramic body by using 3D printing process
JP2017121806A